Isu Kritis Pendidikan Islam di Kawasan ASEAN: Tantangan, Transformasi Digital, dan Strategi Pengembangan - Fiki Vendi Muchasin; Mutiara Sani; Sukari (Lembaga Yasin AlSys, 2026)
Islamic education in the ASEAN region is developing dynamically in line with social change, globalization, and advances in digital technology, but it continues to face structural and pedagogical issues that require comprehensive examination. This study aimed to analyze the development of Islamic education in ASEAN, identify the challenges of globalization and digitalization, and formulate strategies for its development. The study employed a descriptive qualitative approach using a literature review method through the examination of various relevant sources. The findings showed that Islamic education in ASEAN continues to face various critical issues, including the dualism of educational systems, the need for curriculum modernization, limited teacher competence, digital transformation, unequal access to education, limited funding, and the strengthening of religious moderation. The required development strategies include integrating religious and general sciences, reforming curricula based on twenty-first-century competencies, improving teacher competence, using artificial intelligence ethically, accelerating digital transformation, strengthening character education and religious moderation, and enhancing regional collaboration among ASEAN countries. This study concludes that the development of Islamic education in ASEAN needs to be undertaken adaptively, integratively, and collaboratively to respond to global changes without losing its Islamic identity and values. These findings contribute to the development of regional Islamic education studies and can serve as a basis for governments and educational institutions in formulating policies that are more responsive to the challenges of globalization and digitalization.